2012
DOI: 10.1111/hae.12034
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps strength, inter‐extremity difference (IED) and joint status in adult persons with severe haemophilia in different age stages

Abstract: Summary Quadriceps weakness seems to be a hallmark in adult persons with severe haemophilia (PWH). The purpose of this study was to compare PWH and non‐haemophilic controls in different age stages with reference to joint status and quadriceps strength. Further aims were to examine the extent of strength‐specific inter‐extremity‐difference (IED) and the prevalence of abnormal IED (AIED). A total of 106 adults with severe haemophilia (H) and 80 controls (C) had undergone an orthopaedic examination for classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 30 publications
(47 reference statements)
2
35
0
1
Order By: Relevance
“…Regarding strength performance, studies have shown reduced strength in certain muscle groups and patient groups: adults with haemophilia seem to have strength deficits in the upper and lower extremities as well as in the back muscles. This affects especially elderly adults, moderately to severely affected patients and those with a worse joint status . Studies on children and adolescents showed contradictory results which might be connected to the severity of the disease, the factor therapy, the joint affection and the method of examination.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding strength performance, studies have shown reduced strength in certain muscle groups and patient groups: adults with haemophilia seem to have strength deficits in the upper and lower extremities as well as in the back muscles. This affects especially elderly adults, moderately to severely affected patients and those with a worse joint status . Studies on children and adolescents showed contradictory results which might be connected to the severity of the disease, the factor therapy, the joint affection and the method of examination.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of IED in quadriceps strength was calculated as described earlier . In accordance with Sapega and Kannus , side‐to‐side imbalances of muscular strength greater than 20% were classified as AIED.…”
Section: Methodsmentioning
confidence: 99%
“…The weakness of the m. quadriceps femoris in particular is a frequently described problem in several studies . Besides this, also higher inter‐extremity differences (IED) of quadriceps strength were found in people with severe haemophilia (PWH) as well as a high prevalence for abnormal IED (AIED) . Another research revealed a linkage of such an AIED with significant alterations of the patellar tendon .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations